KESAKSIAN PEREMPUAN DALAM QANUN ACEH NO. 7 TAHUN 2013 TENTANG JARIMAH ZINA (Perspektif Hukum Islam dan Gender) - Muhadi Khalidi (Universitas Islam Negeri Ar-Raniry, 2020)
Aceh Qanun Number 7 of 2013 concerning the Jinayat Procedural Law, there is an article which regulates the evidence in the case of jarimah adultery, namely Article 182 paragraph (5) but does not mention the testimony given by women. The formulation of the problem is how Qanun stipulations No. 7 of 2013 concerning the proof in Jarimah Adultery, and how to review the testimony of women in the case of Jarimah Adultery according to the perspective of Islamic Law and Gender. Writing This article is categorized in normative legal research that is a legal research carried out by examining mere literature or secondary data. From the research results obtained reads Article 182 Aceh Qanun No. 7 of 2013 shows that witnesses are evidence. In the context of gender, the testimonies given by women and men are the same. Seeing the testimony as evidence in Islamic law, the differences of opinion between jumhur and Ibn Hazm can be concluded as complementary diversity. The diverse power of witnesses in a case requires that a Judge make a legal discovery